PENGARUH WARNA CAHAYA LAMPU TERHADAP PRODUKSI TELUR BURUNG PUYUH ( Coturnix coturnix japonica ) - Sangi, Jimmy; Saerang, J. L.P; Nangoy, F.J; Laihat, J (Universitas Sam Ratulangi, 2017)
EFFECT OF LIGHT BULB COLOR ON EGG PRODUCTION OF QUAILS Â (Coturnix Coturnix japonica). The present study was conducted to determine the effect of different color of light bulbs on egg production of Quails (Coturnix Coturnix japonica). Â The trial was conducted for seven weeks during the egg laying period. A Completely Randomized Design (CRD) with 4 treatments and 5 replications was used to as experimental design. Treatments were formulated using 5 different light bulb colors, as follow: Â R0 = no color (transparent) light bulb, R1 = yellow color light bulb; R2 = green color light bulb, and R3 = red color light bulb. The variables measured were: feed consumption, egg production, and egg weight. Research results showed that treatment did not significantly (P > 0.05) affect daily feed consumption, egg production, and egg weight. It can be concluded that color differences (transparent, yellow, green, and red) in lighting can be used interchangeably in Quail egg production purposes.Keywords: Light bulb color, Quail, feed consumption, egg production, egg weight